Personality distribution of Canadian medical students: A first look - Harris, June; McKay, Donald (Canadian Medical Education Journal, 2018)
Background: Personality is one of the key elements in professional identity formation and is self-identified as one of the top two influences for Canadian medical graduates when making a specialty choice yet little is known about the personalities of Canadian medical students. This study is the first to report personality data regarding Canadian medical students. Methods: Personality is one of the key elements in professional identity formation and is self-identified as one of the top two influences for Canadian medical graduates when making a specialty choice yet little is known about the personalities of Canadian medical students. This study is the first to report personality data regarding Canadian medical students. Results: The data were analyzed using Chi square. The distribution of personalities [Guardian, Idealist, Artisan, Rational] for medical students differs from the distribution reported for the general Canadian population. The distribution of personalities is similar for each Canadian medical school. Conclusion: Results from this first national accounting of the personalities of Canadian medical students suggest either that the personalities of medical school applicants differ from the general population or that personality affects medical school admissions success. Knowing the personalities of medical students could be important for medical schools in such areas as admissions, career counselling and professional identity formation.